2002
DOI: 10.1029/2001jb001691
|View full text |Cite
|
Sign up to set email alerts
|

Upper crustal seismic structure of the slow spreading Mid‐Atlantic Ridge, 35°N: Constraints on volcanic emplacement processes

Abstract: [1] The upper crustal seismic structure of the slow spreading Mid-Atlantic Ridge is studied using a genetic algorithm-based waveform inversion of multichannel streamer data. Four single-ship multichannel profiles from 35°N are analyzed: one in the rift valley and three in the rift mountains along 0.7, 1.6, and 1.9 Ma crust. A layer 2A horizon is continuously imaged along three profiles and is associated with a sharp velocity increase from extrusives to dikes. Its depth and regularity in the rift valley indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 93 publications
11
63
1
Order By: Relevance
“…The low-velocity layer, seismic layer 2, is usually observed throughout the top 1-2 km of the crust (Barclay et al, 1998;Canales et al, 2000a;Dunn et al, 2005;Hooft et al, 2000;Hosford et al, 2001;Hussenoeder et al, 2002) and is generally accepted to be the result of a high proportion of pores and cracks at these depths. The low-velocity layer, seismic layer 2, is usually observed throughout the top 1-2 km of the crust (Barclay et al, 1998;Canales et al, 2000a;Dunn et al, 2005;Hooft et al, 2000;Hosford et al, 2001;Hussenoeder et al, 2002) and is generally accepted to be the result of a high proportion of pores and cracks at these depths.…”
Section: Slow-spreading Ridgesmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-velocity layer, seismic layer 2, is usually observed throughout the top 1-2 km of the crust (Barclay et al, 1998;Canales et al, 2000a;Dunn et al, 2005;Hooft et al, 2000;Hosford et al, 2001;Hussenoeder et al, 2002) and is generally accepted to be the result of a high proportion of pores and cracks at these depths. The low-velocity layer, seismic layer 2, is usually observed throughout the top 1-2 km of the crust (Barclay et al, 1998;Canales et al, 2000a;Dunn et al, 2005;Hooft et al, 2000;Hosford et al, 2001;Hussenoeder et al, 2002) and is generally accepted to be the result of a high proportion of pores and cracks at these depths.…”
Section: Slow-spreading Ridgesmentioning
confidence: 99%
“…The low-velocity layer, seismic layer 2, is usually observed throughout the top 1-2 km of the crust (Barclay et al, 1998;Canales et al, 2000a;Dunn et al, 2005;Hooft et al, 2000;Hosford et al, 2001;Hussenoeder et al, 2002) and is generally accepted to be the result of a high proportion of pores and cracks at these depths. The seismic structure of the upper crust is laterally variable and appears to reflect a variety of processes, such as tectonic modification, volcanic flux variations, and crustal aging (Arnulf et al, 2012;Barclay et al, 1998;Dunn et al, 2005;Hosford et al, 2001;Hussenoeder et al, 2002;Magde et al, 2000). The seismic structure of the upper crust is laterally variable and appears to reflect a variety of processes, such as tectonic modification, volcanic flux variations, and crustal aging (Arnulf et al, 2012;Barclay et al, 1998;Dunn et al, 2005;Hosford et al, 2001;Hussenoeder et al, 2002;Magde et al, 2000).…”
Section: Slow-spreading Ridgesmentioning
confidence: 99%
“…Several observations indicate that the upper 3–4 km of crust is cool and brittle. A seismic low‐velocity layer observed throughout the top 1–2 km of the crust [ Barclay et al , 1998; Hooft et al , 2000; Canales et al , 2000a; Hosford et al , 2001; Hussenoeder et al , 2002], known as seismic layer 2, is observed here as well as worldwide in the oceans and is generally accepted to be the result of a high proportion of pores and cracks at these depths [e.g., Spudich and Orcutt , 1980; Detrick et al , 1994; Swift et al , 1998]. An analysis of the ratio of P to S wave velocity in the shallow crust and the detection of seismic anisotropy, an indicator of widespread ridge‐parallel extension cracks, reveals that the upper 2 km of crust is pervaded with cracks and is thus relatively cool and brittle [ Barclay et al , 2001; Barclay and Toomey , 2003].…”
Section: Mid‐atlantic Ridge At 35°nmentioning
confidence: 99%
“…The seismic structure of the upper crust is laterally variable and appears to reflect a variety of processes such as tectonic modification, crustal accretion variations, and crustal aging [ Barclay et al , 1998; Magde et al , 2000; Hosford et al , 2001; Hussenoeder et al , 2002]. In contrast to fast spreading ridges where the axis of eruption is fairly narrow (∼1–2 km), formation of new crust appears to occur over the entire width of the axial valley [ Barclay et al , 1998].…”
Section: Mid‐atlantic Ridge At 35°nmentioning
confidence: 99%
“…tectable given our ray set. Seismic re£ection pro¢les in our study area have determined one-dimensional shallow (to depths of 800 m) velocity structures for 11 locations, ranging in age from 0 to 1.9 Ma [23]. Ray tracing through these structures we ¢nd a maximum 1-way variation of 20 ms for vertically propagating P-waves.…”
Section: Resolution Testsmentioning
confidence: 99%